2009
DOI: 10.1080/14616680902827175
|View full text |Cite
|
Sign up to set email alerts
|

The Film Producer as the Long-stay Business Tourist: Rethinking Film and Tourism from a Gold Coast Perspective

Abstract: Studies of the connection between film and tourism have tended to foreground film-induced tourism whether as a consequence of films being made in particular locations or as arguments for encouraging film production activity in a particular location. In both cases film production is seen to be beneficial for the ancillary benefits it creates in terms of destination awareness. In this article, however, we suggest that film-induced tourism is a somewhat limited way of perceiving the relationship between film prod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 20 publications
(16 reference statements)
0
14
0
Order By: Relevance
“…The impact of pop-culture/film induced tourism has been investigated from various perspectives including visitors' experiences, destination image, travel motivation, future behavioral intentions, destination brand construction, and residents' responses (Busby & Klug, 2001;Busby, Brunt, & Lund, 2003;Busby & O'Neill, 2006;O'Connor & Bolan, 2008;Roesch, 2009;Ward & O'Regan, 2009). Film induced tourism has its ability to provide benefits to filmed and portrayed locations because TV shows, media, and films can lead to high market penetration, stimulating interest, formulating destination image, and eventually visiting the destinations (Busby, Huang, & Jarman, 2013;Busby & Klug, 2001;Frost, 2010;Kim, 2012;Shani, Chen, Wang, & Hua, 2010).…”
Section: Popular Culture (Pop-culture) Tourismmentioning
confidence: 99%
“…The impact of pop-culture/film induced tourism has been investigated from various perspectives including visitors' experiences, destination image, travel motivation, future behavioral intentions, destination brand construction, and residents' responses (Busby & Klug, 2001;Busby, Brunt, & Lund, 2003;Busby & O'Neill, 2006;O'Connor & Bolan, 2008;Roesch, 2009;Ward & O'Regan, 2009). Film induced tourism has its ability to provide benefits to filmed and portrayed locations because TV shows, media, and films can lead to high market penetration, stimulating interest, formulating destination image, and eventually visiting the destinations (Busby, Huang, & Jarman, 2013;Busby & Klug, 2001;Frost, 2010;Kim, 2012;Shani, Chen, Wang, & Hua, 2010).…”
Section: Popular Culture (Pop-culture) Tourismmentioning
confidence: 99%
“…Additionally, film place-placement has postproduction effects (PPE) for the location by way of the growth of tourism (Riley, Baker and Van Doren, 1998;Busby and Klug, 2001). Thus, by a location featuring in a film, it can develop two industries, film and tourism (Cynthia and Beeton, 2009;Ward and O'Regan, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…69 Media scholars Susan Ward and Tom O'Regan have likened film personnel in Brisbane, Australia, to long-stay business tourists, a characterization that fits New Orleans's own Hollywood-moneyed class. 70 The buyers of the Whann-Bohn house, for example, may have used public money to build film-production infrastructure, but a glance at reviews on the vacation rental site VBRO by a group of fifteen who came for Mardi Gras confirmed what I already knew: that movie-industry investors had reconfigured urban space to be one of their own personal playgrounds. "I've been to some of the best restaurants in my entire life, " one director raved after coming to New Orleans in 2008.…”
Section: Holly Wo Od South's Star Maps and Tourist Tr Apsmentioning
confidence: 91%
“…Echoing the Progressive vision of the Behrman administration and a M-I-N-O plea for goods made at home, Diamond's success would be "of advantage to the city from a business as well as a sentimental point of view, for the outlays of salaries and supplies would all go into the coffers of local people. " 70 The company's investor handbook reprinted Horatio Alger stories about those in New York and Chicago who had made their fortune in film manufacturing. Diamond repurposed stories in the Times-Picayune about Nola Film to evidence its sure future and the ability of New Orleans to rival Los Angeles, which, according to Diamond, had become overcrowded with studios.…”
Section: Film Ec Onomy Take 4: a Diamond In The Roughmentioning
confidence: 99%